ANALISIS SENGKETA PROSEDUR HUKUM PENDAFTARAN MEREK GEN HALILINTAR - Luqyana Salsabila, (2023)
In this thesis, we will discuss the case in the form of a dispute in the registration of the mark in the form of a rejection of the application for the Gen Halilintar + Lukisan brand, which then a prosecution was carried out by Halilintar Anofial Asmid against the Ministry of Law and Human Rights for the refusal. This research was created to examine how the registration of the Gen Halilintar + Lukisan brand which initially received rejection of its application, but in the end was able to get protection over the brand. In this thesis, the method used in this research is normative juridical, which is a legal research method carried out by examining library materials and secondary data including primary legal sources and secondary sources. The results of this study are about how the existing trademark registration system in Indonesia and the application for trademark registration in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. In addition, in this study there was also a presentation on the analysis of the considerations and court decisions that granted the application for registration of the Gen Halilintar + Lukisan brand.